Inclusión del abandono de lugar del accidente como delito y no como agravante dentro del código orgánico integral penal - Cáceres Villacís, Francisco Anthony (2020)
The objective of this research work is to be able to define the abandonment of the accident site in order to propose a correct classification as an autonomous crime and to stop being considered only as an aggravating circumstance within our criminal legislation, so it will be studied from its historical, doctrinal perspective, which will be mentioned in order to proceed to expose the antecedents and the evolution throughout the history of the abandonment of the place of the accident and how this has been correctly incorporated in the different regulatory penal norms. Likewise we know that in Criminal Law it is always in constant development and evolution for the general good of a society; and that is why it will be shown throughout the investigation that the classification of the abandonment of the accident site as an autonomous criminal type is very important so that the death rate from traffic accidents decreases in a country, as it happens in Neighboring countries such as Peru, where its criminal criminal policy has this crime as one of the most efficient in guaranteeing life and the correct achievement of justice in the face of traffic accidents, for which reason it is very important to analyze its effectiveness in order to propose a reform to our Organic Penal Code………..